CSF‐1 in Osteocytes Inhibits Nox4‐mediated Oxidative Stress and Promotes Normal Bone Homeostasis. (13th June 2019) - Werner, Sherry L; Sharma, Ramaswamy; Woodruff, Kathleen; Horn, Diane; Harris, Stephen E; Gorin, Yves; Lee, Doug‐Yoon; Hua, Rui; Gu, Sumin; Fajardo, Roberto J; Habib, Samy L; Jiang, Jean X
Abstract: CSF‐1 is a key factor in regulating bone remodeling; osteocytes express CSF‐1 and its receptor. Viable osteocytes are essential for bone remodeling through cell–cell contact and secretion of factors that regulate osteoblasts and osteoclasts. Increased oxidative stress contributes to osteocyte death and correlates with bone loss during aging. The NADPH oxidase Nox4 is a major source of ROS in bone. CSF‐1 decreases Nox4, suggesting that CSF‐1 protects against oxidative stress. Here, we show that osteocyte apoptosis previously reported in our global CSF‐1KO mice is associated with increased Nox4, as well as 4‐HNE expression in osteocytes. Osteocytes isolated from CSF‐1KO mice were less viable and showed increased intracellular ROS, elevated NADPH oxidase activity/Nox4 protein, activation of mTOR/S6K, and downstream apoptosis signals compared with WT osteocytes. Nox4 expression was also increased in CSF‐1KO osteocytes and colocalized with MitoTracker Red in mitochondria. Notably, CSF‐1 inhibited Nox4 expression and apoptosis cascade signals. In additional studies, shNox4 decreased these signals in CSF‐1KO osteocytes, whereas overexpression of Nox4 in WT osteocytes activated the apoptosis pathway. To determine the role of CSF‐1 in osteocytes, DMP1Cre‐CSF‐1cKO (CSF‐1cKO) mice that lack CSF‐1 in osteocytes/late osteoblasts were developed. Osteocyte defects in CSF‐1cKO mice overlapped with those in CSF‐1KO mice, including increased apoptosis, Nox4, and 4‐HNE‐expressing osteocytes. CSF‐1cKO mice showed unbalanced cancellous bone remodeling with decreased bone formation and resorption. Continued exposure to high Nox4/ROS levels may further compromise bone formation and predispose to bone loss and skeletal fragility. Taken together, our findings suggest a novel link between CSF‐1, Nox4‐derived ROS, and osteocyte survival/function that is crucial for osteocyte‐mediated bone remodeling. Results reveal new mechanisms by which CSF‐1/oxidative stress regulate osteocyte homeostasis, which may lead to therapeutic strategies to improve skeletal health in aging. © 2018 American Society for Bone and Mineral Research